An unusual 7 cm large typical carcinoid managed by surgery: a rare case report - Khan, Nafees Ahmad; Firdaus, Huma; Lall, Ajay; Kumar, Jaya (International Journal of Research in Medical Sciences, 2020)
Carcinoid tumors of the lung are uncommon group of pulmonary neoplasms. Most common site is gastrointestinal tract followed by lungs. Typical pulmonary carcinoids are usually small as described in various case series size of a typical carcinoid may ranges from 0.5-2 cm and are managed surgically. Here we present a case of unusually large typical carcinoid measuring up to 7 cm which was managed surgically.